Collisional Rate Parameters for the $1s_4$ Energy Level of Neon 638.3 nm and 650.7 nm Transitions from the Analyses of the Time-Dependent Optogalvanic Signals (Journal of Atomic and Molecular Sciences, 2010)
A mathematical rate equation model using a Monte Carlo simulation has been used to analyze the laser optogalvanic signals of neon waveforms excited at 638.3 nm and 650.7 nm and arising from the $1s_{4}$ state transitioning to $2p_{7}$ and $2p_{8}$ states, respectively. The decay rates have been determined for the directly involved $1s_{4}$ state and also for the indirectly involved $1s_{2}$ and $1s_{5}$ states. There is good agreement among the decay rate constants found and they show a predominantly linear variation with increasing current.
Keywords: optogalvanic effect; Monte Carlo least-square fitting; collisional rates.